Factors influencing consumer purchase decision towards Peugeot car / Noor Haliza Abdul Rahman - Abdul Rahman, Noor Haliza (2013)
The purpose of this study is to identify the factors influencing customer purchase decision toward Peugeot car and to investigate the relationship of the selected independent variable, price, quality, brand image and after sale service with dependent variables factor which is purchase decision. In order to provide a guide for this study, four hypotheses were formulated. Data were collected from 100 respondents of customers in Murni Millena Sdn Bhd in Kota Bharu by using questionnaires. Result obtain from the descriptive statistic revealed that most of the respondent agree with the selected independent variable and correlation analysis revealed that all independent variables which is price, quality, brand image and after sale service have moderate to high correlation with the dependent variable which is purchase decision. This supported by regression analysis where the R2 is equal to 0.633 which indicates 63.3 % of the variances in the dependent variable which is purchase decision can be explained by changes in the independent variables, the other 36.7% cannot be explained by the independent variables which are price, quality, brand image as well as after sale service. The findings from hypothesis testing show that the null hypothesis is rejected and alternate hypothesis is accepted. It can be concluded that there are relationship between purchase decision and selected independent variables of the study appeared to provide significant result.